1998
DOI: 10.1128/aem.64.7.2697-2700.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of SYTOX Green Stain for Bacterial Viability Assessment

Abstract: The effectiveness of SYTOX Green nucleic acid stain for measuring bacterial viability was tested on starved populations of Escherichia coli and Salmonella typhimurium. This stain underestimates the fraction of dead cells within starved populations containing cells with damaged nucleic acids or membranes. Its application to natural samples should be considered with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 19 publications
3
102
0
4
Order By: Relevance
“…Heating of samples is used for verification of viability methods (Deere et al 1995;Roth et al 1997;Lebaron et al 1998), and the present results confirmed that membranes, nucleic acids and certain enzymes are cellular sites of heat injury (Teixeira et al 1997).…”
Section: Light-irradiatedsupporting
confidence: 71%
See 1 more Smart Citation
“…Heating of samples is used for verification of viability methods (Deere et al 1995;Roth et al 1997;Lebaron et al 1998), and the present results confirmed that membranes, nucleic acids and certain enzymes are cellular sites of heat injury (Teixeira et al 1997).…”
Section: Light-irradiatedsupporting
confidence: 71%
“…It was recently reported (Lebaron et al 1998) that the SYTOX Green assay under-estimates the fraction of dead cells within starved populations of E. coli and Salmonella typhimurium. Several permeabilized (dead) cells had damaged nucleic acids and could therefore not accumulate more SYTOX Green nucleic acid stain than the less permeable, living cells.…”
Section: Effect Of Pre-uv Light Irradiation and Starvationmentioning
confidence: 99%
“…Sytox green constitutes a high affinity nucleic acid stain that does not cross the membranes of live cells, but it enters into the membranes of cells with compromised plasma membrane. This dead cell marker has shown its effectiveness as an indicator of assessment after the exposure of cells to antimicrobial agents (Roth et al 1997;Lebaron et al 1998). Thus, concentrated supernatants from Lact.…”
Section: Discussionmentioning
confidence: 99%
“…Although SYTOX Green (S-7020, Invitrogen-Molecular Probes, Eugene, OR) has been used extensively with eukaryotes and heterotrophic bacterial cells (Lebaron et al, 1998;Brussaard et al, 2001;Veldhuis et al, 2001;Klauth et al, 2004), there are few examples of its use with cyanobacteria . Therefore, trial testing was neces-sary with many different strains to determine the effectiveness of SYTOX Green and the appropriate concentration.…”
Section: Sytox Green Analysismentioning
confidence: 99%